PEMANFAATAN ARANG AKTIF DARI TEMPURUNG Jatropha curcas L. YANG TERMODIFIKASI SEBAGAI ADSORBEN LOGAM TEMBAGA (Cu) - Teguh Wirawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2010)
A research on the application of activated carbon from Jatropha curcas L shell which is modified as the copper adsorbent has been conducted. The research was varied by series of initial pH 1, 2, 3, 4, and 5 and the contact time 15, 30, 60, 90, and 120 minutes and its effect to copper adsorption by activated and modified carbon from Jatropha curcas L shell. The result showed that the optimum pH for AA-FISIK, AA-EDTA and AA-HNO3 is 3 and for AA-HCl is 5. The optimum contact time is 90 minutes for AA-HCL and AA-EDTA; 60 minutes for AA-HNO3; and 120 minutes for AA-PHYSICAL. It was also found that higher initial concentration will increase the total amount of adsorbed copper.Keywords: adsorption, copper, activated carbon, Jatropha curcas L